Mamey Sapote from Florida - A. R. Rafie; Jonathan Crane; Carlos Balerdi; Steven Sargent (EDIS)
HS-1103, a 2-page illustrated fact sheet by A. R. Rafie, Jonathan Crane, Carlos Balerdi, and Steven Sargent, describes this fruit, how to pack it for shipment, supply, postharvest life, and preparation. Includes a table indicating seasonal availability of mamey sapote from Florida. Published by the UF Department of Horticultural Sciences, June 2007.